Perancangan 5R di Gudang dan Area Produksi Fleksibel PT Indoceria Plastic & Printing - Christoffel Christoffel (Jurnal Titra, 2021)
PT Indoceria Plastic & Printing is still in the 5R design stage in the logistics area and Flexible Production area for its employees. The problem faced by the Indoceria Company is that the Company is still not clean, has not been well organized and has not yet cultivated the 5R method, so that operator performance cannot be maximized. The effort that can be done in improving company performance is by designing the 5R method. The design and implementation of 5R carried out in this Final Project is to clean the factory area, tidy up the equipment in factory, make a storage place for equipment and make 5R aids in the form of hygiene posters, 5R posters. The final results of the implementation of 5R companies are getting better.